A Possible Larva of Lepicerus inaequalis Motschulsky (Coleoptera: Myxophaga: Lepiceridae) from Panama - Lawrence, John F.; Ślipiński, Adam; Beutel, Rolf G.; Newton, Alfred F. (Zootaxa, 2013)
A larva is described which is presumed to be that of Lepicerus inaequalis Motschulsky based on several probable first instars and one later instar collected a few miles from and in a similar habitat to adult specimens of this species. The association is additionally based on several features also occurring in other known myxophagan larvae. A key is provided comparing these larvae with those of the other three families of Myxophaga.